Calculation of aircraft impact load on the NPP nuclear island buildings - Novozhilov, Yuriy Vladislavovich; Mikhaluk, Dmitriy Sergeyevich; Feoktistova, Lyudmila Yur’yevna (Computational Continuum Mechanics, 2018)
The IAEA safety requirements require that the design of nuclear power plants (NPPs) considers both the potential technological disaster and acts of nature. One of the applicable mandatory IAEA SRS 87 requirements is assessing the risk of heavy commercial aircraft crashing into or attacking nuclear power plant reinforced concrete structures. The standards determine the distribution of loads on the building structures as a result of the impact of such aircrafts as the Boeing 720 and the Boeing 707-320. In the simplest case, when an aircraft strikes a plane low-deformable target normally, the structural load can be considered directly as a distributed force mapped on the target face. However, when an aircraft strikes at a tangent to the surface of the structure or when the load is imposed on the surface of complex-geometry structures or the possibility of successive target penetration needs to be considered, this loading method is useless. This paper suggests a universal methodology for modeling the loads imposed on building structures as a result of an aircraft impact. Aircraft modeling is based on the Eulerian formulation of the finite element method (FEM). The obtained relations can be used to identify the geometry, structural and mass parameters of the finite element aircraft model for a given load and determined impact imprint. The comparison of specified pressure loads and impact loads on the reinforced concrete structure shows a close match of the results. The obtained mathematical model of a heavy commercial aircraft can be used for numerical simulation of an aircraft crash into NPP buildings and structures in accordance with the new IAEA requirements.